Specification of one classical fingerprint of ideal memristor. Issue 4 (April 2015) - Biolek, Z.; Biolek, D.; Biolková, V.
Abstract It is well known that the memristor hysteresis vanishes if the frequency of its sinusoidal excitation increases. Such a regularity is frequently interpreted as one of the most widely known fingerprints of the memristor. Specifying this fingerprint, the paper yields a new piece of knowledge about the frequency dependence of hysteresis for a constant amplitude of the excitation.